The Texan's promise - Navarro, Jolene (Navarro, Jolene. Cowboys of Diamondback Ranch., 2020)
"When a lightning storm lands Quinn Sinclair on single mom Belle De La Rosa's ranch, she finds herself drawn to the handsome conservationist and his children. Belle isn't looking for love--not while she's trying to sell part of her ranch to developers to stay afloat. But when she discovers that Quinn's purpose in town is to stop the sale, can she trust him...with her heart?"--Publisher's promotional description.